ADSORPTION OF COPPER ON SURFACES OF FEASIBLE MATERIALS (PLANT WASTE, SLUDGE AND BENTONITE) METAL) - Al-Hayani, A.S. J. Z.; Al-Hassoon, S. N.H.; Al-Obaidi, M.A.J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Extraction of Copper ion from its water solutions using plant waste (compost), sludge and Bentonite metal as cheap natural adsorbed materials. It was found that Copper ion extraction was based on concentration of Copper and amount of the adsorbed materials. Highest amount of adsorption was obtained at 180 µg Cu ml-1 as Bentonite, plant waste and sludge respectively. Thermal equilibrium of the system was studied by Langmuir equation, R2 gave a good linear relationship in succession. Maximum regulatory capacity and regulatory capacity at equilibrium is 1.0 , 0.99 and 0.96 to plant waste, sludge and Bentonite respectively, as the preference coefficient constant calculated by the Langmuir equation indicate that adsorption is preferable and irriversible for plant waste and sludge while not preferentially and reversible for bentonite. G adsorption reactions were automatic for the Bentonite metal, while for plant waste and sludge non-spontaneous reaction and needs extra activation energy. It is clear from the above that the use of natural materials in the extraction of copper ion is a very effective method and it is an inexpensive and friendly methods envirooment.